(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The objective of the research is to identify the nature of voluntary disclosure of insurance services and its impact on the financial performance of Iraqi insurance companies by knowing the relationship between increasing disclosure of financial services and financial performance indicators of insurance companies.In order to achieve this objective, the research was applied to a sample of the Iraqi insurance companies listed in the Iraqi Stock Exchange (Al Amin Insurance Company, Al Ahlia Insurance, Dar Al Salam Insurance, Gulf Insurance, Al Hamra Insurance) and based on their published financial statements (2014-2015) ) And by analyzing the sample lists were connected to the research objectives.The main conclusion of the study is that insurance companies’ disclosure of insurance services to customers affects their financial performance in a manner that leads to their future growth.The most important recommended by the research is the need for Iraqi insurance companies to provide more information about the insurance services provided to customers through the lists and financial reports final, and recommended the use of indicators of financial analysis to know the impact of the process of optional disclosure on the performance directly.